Detection of early FXTAS motor symptoms using the CATSYS computerised neuromotor test battery. Issue 5 (30th January 2008) - Allen, E G; Juncos, J; Letz, R; Rusin, M; Hamilton, D; Novak, G; Shubeck, L; Tinker, S W; Sherman, S L
Abstract : Background: Carriers of the FMR1 premutation allele are at a significantly increased risk for a late-onset neurodegenerative disorder, fragile X-associated tremor/ataxia syndrome (FXTAS). This disorder is distinct from fragile X syndrome (FXS) in its molecular aetiology and clinical presentation. The primary features of FXTAS are late-onset intention tremor and gait ataxia. Associated features include parkinsonism, neuropsychological dysfunction, autonomic dysfunction and peripheral neuropathy. Aim: To investigate the usefulness of a quantitative neurological test battery implemented through the CATSYS instrument to identify preclinical symptoms of FXTAS. Methods: Both premutation carriers with 70–199 repeats (62 men) and their low-repeat allele carrier siblings (27 men), identified through families with an individual affected with FXS, were tested. Results: As expected, because of its sensitivity, use of the instrument allowed identification of tremor in 23% of men who had not self-reported tremor, and ataxia in 30% of men who had not self-reported ataxia. Among subjects with self-reported tremor and ataxia, we found significant concordance between measures of the CATSYS system and the self-report. Conclusion: Rates of these traits among premutation carriers and low-repeat allele carrier siblings could be identified, and are presented in this paper, along with the minimum estimates of age-related prevalence.